Legal Politics of Judicial Supervision Constitution - Krismanto Manurung; Ismaidar Ismaidar; Tamaulina Br. Sembiring (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
In order to preserve and uphold the honor, dignity, and the behavior of the judge is required to supervise the attitude of the constitutional judge to fit the code of ethics, so that each judge's ruling will be implemented in order to enforce the law and justice based on Pancasila and the Constitution 1945 asapermanent legal political for supervision of the constitutional judges . Meanwhile legal politics incidental that becomes a choice among others: a) Behavior of Constitutional Judges are supervised by the Board of Ethics established by the Constitutional Court, and for the reported judges or suspected violations of ethic codes of Constitutional Judges formed by Honorary Council of Constitutional Judges who were proposed by Ethics Council, with the task of implementing and serving as judicial ethic; and b) there is no judicial supervision against Constitutional Court's decision as well as supervision of a court decision which was in the Supreme Court through the mechanism of legal remedies ( ordinary and extraordinary).